COSTA RICAN NATIONAL EXHIBITIONS 1917-1918 - Urbina Gaitán, Chester (2013)
The National Exhibitions of 1917 and 1918 were used by FedericoTinoco regime to make good political image for to present at Costa Rica as an agricultural country, peaceful and polite. The political most awarded figure in the artistic works of these events was Mr. Mauro Fernandez, due to the interest of the dictatorship tinoquista for try to overcome of the political crisis in which it was immersed.